System approach to games and competitive playing: Reply to Lebed (2006) - McGarry, T.; Franks, I. M. (European Journal of Sport Science, 2007)
In this article, we respond to some criticisms by Lebed (2006) of our previous research (McGarry, Anderson, Wallace, Hughes, & Franks, 2002) in which we reported that (a) the space-time interactions of players in sports (squash) contests might usefully be considered as a dynamical system, (b) that the other racket sports of tennis and badminton might likewise subscribe to a similar description, and (c) that doubles-play in these same racket sports might further be explained using the same self-organizing principles. From there, we speculated that team sports (taking soccer as an example) might ultimately also subscribe to similar principles, thus offering the possibility of a common underpinning for the space-time movements of sports players that seemingly give rise to patterned behaviours that are nonetheless unique. Lebed (2006) criticized this interpretation of sports (squash) contests as a dynamical system and instead offered a different account, though unfortunately these criticisms are inaccurate and unfounded. The most important point overlooked by Lebed (2006), and thus reiterated here, is that the essentials for a dynamical system - namely, the presence of coupled oscillators that comprise the system, as well as the sharing of information among the coupled oscillators that produces the patterned formations - are present in the racket sports for both singles-play and doubles-play. The presence of these essentials for team sports, however, must remain a matter of speculation for the time being as noted previously (McGarry et al., 2002).